Regulatory delays in a multinational clinical stroke trial. (June 2021) - de Jonge, Jeroen C; Reinink, Hendrik; Colam, Bridget; Alpers, Iris; Ciccone, Alfonso; Csiba, Laszlo; Kõrv, Janika; Kurkowska-Jastrzebska, Iwona; Macleod, Malcolm R; Ntaios, George; Thomalla, Götz; Bath, Philip M; et al.
Introduction: The initiation and conduct of randomised clinical trials are complicated by multiple barriers, including delays in obtaining regulatory approvals. Quantitative data on the extent of the delays due to national or local review in randomised clinical trials is scarce. Materials and methods: We assessed the times needed to obtain regulatory approval and to initiate a trial site for an academic, EU-funded, phase III, randomised clinical trial of pharmacological prevention of complications in patients with acute stroke in over 80 sites in nine European countries. The primary outcome was the time from the first submission to a regulatory authority to initiation of a trial site. Secondary outcomes included time needed to complete each individual preparatory requirement and the number of patients recruited by each site in the first 6 and 12 months. Results: The median time from the first submission to a regulatory authority to initiation of a trial site was 784 days (IQR: 586–1102). The single most time-consuming step was the conclusion of a clinical trial agreement between the national coordinator and the trial site, which took a median of 194 days (IQR: 93–293). A longer time to site initiation was associated with a lower patient recruitment rate in the first six months after initiation (B = –0.002; p = 0.02). Discussion: Conclusion: In this EU-funded clinical trial, approximately 26 months were needed to initiate a trial site for patient recruitment. The conclusion of a contract with a trial site was the most time-consuming activity. To simplify and speed up the process, we suggest that the level of detail of contracts for academic trials should be proportional to the risks and commercial interests of these trials.